1986
DOI: 10.1126/science.231.4736.346
|View full text |Cite
|
Sign up to set email alerts
|

Electrons in Silicon Microstructures

Abstract: Silicon microstructures only a few hundred atoms wide can be fabricated and used to study electron transport in narrow channels. Spatially localized voltage probes as close together as 0.1 micrometer can be used to investigate a variety of physical phenomena, including velocity saturation due to phonon emission, the local potentials caused by scattering from a single trapped electron, and quantum tunneling or hopping among very few electron states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Current and projected cell sizes for DRAMS are: 1 megabit (1 Mb), now commercially available, 30 pm2; 4 Mb, 1989, 13 pm2;16 Mb, 1992, 5 pm2;64 Mb, 1995,2 pm2 (Robinson, 1986a. Research structures have been reported with features nearly 100 times smaller than those used in commercial integrated circuits (Howard et al, 1986). A transistor that recently set a speed record of 6-ps switching time had an undoped gallium arsenide spacer layer of 20 to 40 A (Robinson, 1986b).…”
Section: Introductionmentioning
confidence: 99%
“…Current and projected cell sizes for DRAMS are: 1 megabit (1 Mb), now commercially available, 30 pm2; 4 Mb, 1989, 13 pm2;16 Mb, 1992, 5 pm2;64 Mb, 1995,2 pm2 (Robinson, 1986a. Research structures have been reported with features nearly 100 times smaller than those used in commercial integrated circuits (Howard et al, 1986). A transistor that recently set a speed record of 6-ps switching time had an undoped gallium arsenide spacer layer of 20 to 40 A (Robinson, 1986b).…”
Section: Introductionmentioning
confidence: 99%
“…There are many similarities between the propagation of light through disordered microstructures and that of electrons through disordered wires. It has been shown, at very low temperatures, that the conductance of disordered wired fluctuates in much the same way as speckle, and the mathematical treatment of conductance fluctuations is identical to that of speckle [78][79] [80]. Given this, I can imagine that it would be possible to use POWFs to generate unique identifiers using silicon microstructures.…”
Section: Future Workmentioning
confidence: 99%
“…After some years Cheung, Gefen and Riedel [5] studied in detail the function dependences of the persistent current with respect to the temperature, flux, ring circumference, chemical potential and the randomness in the analytical calculations and computer simulations. Their calculations conf'wmed further the idea presented by Landauer et al Up to now, the existence of the persistent current has been justified by many experiments [6][7][8][9][10][11][12][13].…”
mentioning
confidence: 70%
“…In the past decades, the quantum interference effects in mesoscopic systems have been extensively discussed theoretically and measured experimentally with the study of electric conductances and persistent currents [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%